2004
DOI: 10.1002/pd.935
|View full text |Cite
|
Sign up to set email alerts
|

Campomelic acampomelic dysplasia presenting with increased nuchal translucency in the first trimester

Abstract: This is the first report of a fetus affected with campomelic acampomelic dysplasia presenting with increased nuchal translucency. Ultrasonography at 13 weeks of amenorrhea showed a nuchal translucency 5.6 mm thick. The karyotype performed on amniotic fluid cells was normal (46,XY). Ultrasonography at 22 weeks revealed a normal femoral length and female genitalia. A second amniocentesis was performed to confirm the karyotype and for dosage of steroid hormones. Testosterone dosage was low, corresponding to a fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…The transactivating activity of p.Arg394Gly and p.Arg437Cys mutants was compared to that of the known ACD ‐associated SOX 9 mutant p.Pro176Leu (Michel‐Calemard et al. 2004). The results are expressed as the mean ± one standard deviation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The transactivating activity of p.Arg394Gly and p.Arg437Cys mutants was compared to that of the known ACD ‐associated SOX 9 mutant p.Pro176Leu (Michel‐Calemard et al. 2004). The results are expressed as the mean ± one standard deviation.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we compared the transactivating activity of newly identified mutants to that of the known ACD‐associated SOX9 mutant c.527C>T (p.Pro176Leu) (Michel‐Calemard et al. 2004). We used a PGL3 reporter vector (Promega, Madison, WI) containing the murine Amh promoter sequence (from −231 to 0 to the transcription start site of Amh , NC_000076.6) and a PGL4 reporter vector (Promega) containing the murine Col2a1 enhancer sequence (from +1958 to +2485 to the transcription start site of Col2a1 , NC_000081.6).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While a clear genotypephenotype correlation could not be established to date, the acampomelic form appears to be mild by comparison. Of 11 ACD cases in the literature in whom SOX9 mutations were reported, five carry missense mutations (Friedrich, et al, 2000;Michel-Calemard, et al, 2004;Moog, et al, 2001;Sock, et al, 2003; while the other six carry deletions or rearrangements directly affecting a cis-acting element upstream of the SOX9 coding region but not the coding region itself (Hill-Harfe, et al, 2005;Lecointre, et al, 2009;Leipoldt, et al, 2007;Ninomiya, et al, 1996;Velagaleti, et al, 2005). Of 8 cases with ACD and a XY karyotype, 4 cases (1 balanced translocation with a breakpoint upstream from the coding region, 3 missense mutations) do not show sex reversal.…”
Section: Introductionmentioning
confidence: 99%
“…Its antenatal diagnosis is more difficult to make [11] . CD may be suspected after ultrasonography discloses shortened lower limbs and femoral angulation.…”
Section: Introductionmentioning
confidence: 99%